P284 Identifying patients at risk of acute exacerbation of ipf using the cpi score. (15th November 2016) - Fraser, E; Noble, V St; Benamore, R; Hoyles, R; Ho, LP
Abstract : Introduction: Disease course in IPF is punctuated by acute declines, often termed acute exacerbations of IPF (AEIPF) and portends to a mortality of 80% within 3 months. The cause of AEIPF is poorly understood; and there is currently no effective treatment. There is an urgent need to understand the causes and to characterise the parameters that identify patients at risk of AEIPF. Because lung function (DLCO and FVC) and CT imaging are the most accessible (potential) methods for identification of patients at risk of AEIPF, we question if these could be used to identify patient at risk of AEIPF. We explored the utility of the CPI 1 (composite physiological index) for this purpose. Methods: Patients with IPF diagnosed by clinico-pathologic-radiological criteria, according to the 2011 ATS/ERS/JRS/ALAT guidelines, with definite or probable diagnosis of IPF were recruited over a one year period, and divided into stable (n = 12) and AEIPF (n = 8) groups. AEIPF was defined as: 1) deterioration in dyspnoea over 30 days or less 2) new airspace infiltrates on HRCT (with or without evidence of infection) 3) exclusion of pulmonary emboli and heart failure. Lung function (FVC and DLCO) and CPI at 12 months before recruitment and rate of change of FVC within these 12 months were determined. Results and discussion: Patients with AE-IPF had a significantly higher CPI; (mean ± SD) – 62 ± 13 vs stable 45 ± 7; p = 0.001. In contrast, there was no significant difference in FVC levels between the two groups – 61 ± 4% predicted in AE-IPF group vs 72 ± 3% in stable; p = 0.07. CPI but not FVC or DLCO was worse 12 months prior to recruitment in the AEIPF group. Rate of loss in FVC in the year before AEIPF was not significantly different from those with stable disease Conclusions: Early findings suggest that in contrast to DLCO and FVC, high CPI is associated with occurrence of AEIPF within a year. Rate of FVC loss did not correlate with AEIPF in this small study. CPI could be a more sensitive predictor for AEIPF than FVC and DLCO but larger numbers and a prospective study will be required to test this concept. Reference: Wells AU. AJRCCM 2003.